Cyclophosphamide immunosuppression during lymphotropic herpesvirus infection in the guinea pig model. A histopathologic and virologic study. - McCormick, S. (1987)
Guinea pigs infected with lymphotropic herpesvirus (GPHLV) were given the immunosuppressive agent cyclophosphamide (Cy). All Cy-treated animals revealed the expected lymphoid depletion of spleen and lymph node B zones. Acute GPHLV infection of Cy-treated animals resulted in increased blood and spleen leukocyte viral infectivity titers and lymphoid tissue lesions containing cells positive for GPHLV antigen and intranuclear inclusions. During latent GPHLV infection, Cy treatment resulted in declining leukocyte viral infectivity titers without pathologic lesions. Morphologic data suggest that tissue histiocytic cells may be involved in the productive viral infection observed in Cy-immunosuppressed animals during acute GPHLV infection. During latency, however, infectious virus appears restricted to a Cy-sensitive, probably lymphoid, cell. This animal model appears useful for the study of lymphotropic viral infection during immunosuppression.